Penerapan Metode Weight Product (WP) dalam Seleksi Penerima Beasiswa di SMAT Insan Hanifa Sumber Payung - Faruq Kushartono (Alpha-Epsilon: Journal of Mathematics, 2025)
This study aims to design a decision support system for identifying scholarship recipients using the Weighted Product method at SMAT Insan Hanifa Sumber Payung. The Weighted Product (WP) method is a commonly used technique in decision-making. Out of a total of 42 students, the decision support system will select 15 eligible students for the scholarship based on calculations using the WP method. The research results show that D31 achieved the highest score with a value of 0.030735641. This indicates that student D31 and 14 other students meet the criteria set as potential scholarship recipients. Additionally, the designed system is also rated well with a satisfaction level of 86.1%